Pengenalan dan Pelatihan Investasi di Pasar Modal Sebagai Salah Satu Alternatif Investasi Selain di Perbankan - Zulkifli; Fendi Saputra (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
This activity aims to provide knowledge to start investing from an early age for people who have not invested in the capital market. Therefore, the themed activities “Introducing Investment in the Capital Market as an Alternative to Investment Apart from Banking” is expected to be a solution for the community to choose which investment is feasible. The material presented includes basic knowledge about investing in the capital market, investment goals, types of investment both real assets and financial assets, what is the initial process of becoming an investor and next, how to make transactions with the mechanism and characteristics of stock trading in accordance with the rules in force in the capital market. The results of the activity can be seen from the increased knowledge of the participants by investing in the capital market, participants still have difficulty understanding stock investments with trading mechanisms and characteristics, and the ability of participants to master the material is still lacking due to the short time in delivering the material so that participants are still interested in wanting to know more about investing in the capital market. At the end of the community service activity, we conducted an evaluation after delivering the introduction to investment in the capital market and provide the opportunity for participants to ask questions to make them interested in investing in the capital market. The success of this activity can be measured by the number of participants who ask questions. Participants also shared their experiences with investing in banking and insurance so that the participants will try to start investing in stocks.